The binding mode of picrotoxinin in GABAA-ρ receptors: Insight into the subunit's selectivity in the transmembrane domain. (October 2016) - Naffaa, Moawiah M.; Samad, Abdul
Graphical abstract: Picrotoxinin and the residues in green and red colors line the binding sites in the transmembrane regions of ρ1 and ρ2 models, respectively. The current structural study explores for the first time the binding mode of picrotoxinin as a non-competitive antagonist at GABAA-ρ receptors. The selective and potent picrotoxinin at ρ2 GABAc over ρ1 homomeric receptors is predicted to form hydrogen bonds and several hydrophobic interactions as the major contributors for the ligand stabilizing in the TM domain of GABAA-ρ ion channels. The picrotoxinin-residues interactions in the various studied binding modes have expanded our knowledge about the intra-selectivity of ρ subunit-forming homomeric receptors in terms of structure and function. Highlights: The first structural study to reveal the binding mode of picrotoxinin at the TM domain of GABAA-ρ receptors. The interactions of picrotoxinin with residues at 2' sites are essential for the selectivity of this ligand at GABAA-ρ homomeric receptors. The hydrogen bonds and several hydrophobic interactions of picrotoxinin in its binding site are responsible for the ligand activity at GABAA-ρ receptors. Emodel Glide predicted the selectivity of picrotoxinin at GABAA-ρ receptors. Abstract: The channel blocker picrotoxinin has been studied with GABAA-ρ1 and GABAA-ρ2 homology models based on the GluCl crystal structure. Picrotoxinin is tenfold more potent for GABAA-ρ2 than for GABAA-ρ1 homomeric channels. This intra-subunit selectivity arises from the unconserved residues at the 2' sites, which are the essential molecular basis for both the binding and potency of picrotoxinin. The serine residues at the 2' positions of the ρ2 channel are predicted to form multiple hydrogen bonds and hydrophobic interactions with picrotoxinin, whereas the proline residues in the 2' positions of ρ1 channels are predicted to form only hydrophobic contacts with picrotoxinin. However, although the studied ρ1 P2'G, A, and V models form no hydrogen bonds with picrotoxinin, they may participate in several hydrophobic interactions, and the ligand may have distinctive binding modes with GABAA-ρ mutant channels. Picrotoxinin has a lower Emodel value with ρ2 than ρ1 homomeric models (−47 Kcal/mol and −36 Kcal/mol, respectively), suggesting that picrotoxin blocks the pores of the ρ2 channels more effectively.